2024
DOI: 10.1039/d3bm01283b
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen vacancy healing boosts the piezoelectricity of bone scaffolds

Fangwei Qi,
Huixing Li,
Xiuwen Gao
et al.

Abstract: A self-powered stimulated scaffold was constructed by eliminating oxygen vacancies in BaTiO3 to enhance its piezoelectric performance, and the enhanced electrical output effectively accelerated cell proliferation and differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…The diffraction peak of rGO could not be found, which might be due to the fact that the insertion of Cu 2 O led to a decrease in the interlayer spacing of graphite and prevented GO re-accumulation [ 34 ]. Raman spectra were carried out to verify the effective reduction of GO into rGO, as shown in Figure 2 c. The analysis showed that the intensity ratios ( I D / I G ) in Cu 2 O@rGO (1.03) are far higher than those in GO (0.91), suggesting the formation of more sp 3 defects [ 35 , 36 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…The diffraction peak of rGO could not be found, which might be due to the fact that the insertion of Cu 2 O led to a decrease in the interlayer spacing of graphite and prevented GO re-accumulation [ 34 ]. Raman spectra were carried out to verify the effective reduction of GO into rGO, as shown in Figure 2 c. The analysis showed that the intensity ratios ( I D / I G ) in Cu 2 O@rGO (1.03) are far higher than those in GO (0.91), suggesting the formation of more sp 3 defects [ 35 , 36 , 37 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…For convenience, the scaffold was defined as AuKN-LA/PLLA. Additionally, PLLA, KN/PLLA, and AuKN/PLLA scaffolds were fabricated as well …”
Section: Materials and Methodsmentioning
confidence: 97%
“…Additionally, PLLA, KN/PLLA, and AuKN/PLLA scaffolds were fabricated as well. 32 2.4. Characterization.…”
Section: Preparation Of Aukn and Aukn-lamentioning
confidence: 99%
“…This also proves that BaTiO 3 has good biocompatibility, similar to the results reported in studies. 39,40 In addition, the effect of piezoelectric stimulation on cell proliferation in the PMMA and 15 wt % BaTiO 3 group was further evaluated. The MTT assay (Figure 3e) was used to detect the proliferation of cells in the control group, PMMA group, nonpiezoelectric-stimulated PMMA and 15 wt % BaTiO 3 group, and piezoelectricstimulated PMMA and 15 wt % BaTiO 3 group.…”
Section: Cell Compatibility and Osteogenic Differentiationmentioning
confidence: 99%